Subnormothermic ex vivo lung perfusion attenuates ischemia reperfusion injury from donation after circulatory death donors - Arni, Stephan (PLoS One, 2021)
Use of normothermic ex vivo lung perfusion (EVLP) was adopted in clinical practice to assess the quality of marginal donor lungs. Subnormothermic perfusion temperatures are in use among other solid organs to improve biochemical, clinical and immunological parameters. In a rat EVLP model of donation after circulatory death (DCD) lung donors, we tested the effect of four subnormothermic EVLP temperatures that could further improve organ preservation. Warm ischemic time was of 2 hours. EVLP time was of 4 hours. Lung physiological data were recorded and metabolic parameters were assessed. Lung oxygenation at 21°C and 24°C were significantly improved whereas pulmonary vascular resistance and edema formation at 21°C EVLP were significantly worsened when compared to 37°C EVLP. The perfusate concentrations of potassium ions and lactate exiting the lungs with 28°C EVLP were significantly lower whereas sodium and chlorine ions with 32°C EVLP were significantly higher when compared to 37°C EVLP. Also compared to 37°C EVLP, the pro-inflammatory chemokines MIP2, MIP-1α, GRO-α, the cytokine IL-6 were significantly lower with 21°C, 24°C and 28°C EVLP, the IL-18 was significantly lower but only with 21°C EVLP and IL-1β was significantly lower at 21°C and 24°C EVLP. Compared to the 37°C EVLP, the lung tissue ATP content after 21°C, 24°C and 28°C EVLP were significantly higher, the carbonylated protein content after 28°C EVLP was significantly lower and we measured significantly higher myeloperoxidase activities in lung tissues with 21°C, 24°C and 32°C. The 28°C EVLP demonstrated acceptable physiological variables, significantly higher lung tissue ATP content and decreased tissue carbonylated proteins with reduced release of pro-inflammatory cytokines. In conclusion, the 28°C EVLP is a non inferior setting in comparison to the clinically approved 37°C EVLP and significantly improve biochemical, clinical and immunological parameters and may reduce I/R injuries of DCD lung donors.